Can orthodontic need cause bullying? - VIEIRA,Ana Kátia Altoé (2021)
ABSTRACT Objective: To determine the association between orthodontic treatment need and the self-reported bullying, and its impact on adolescents’ self-esteem. Methods: The sample consisted of 160 schoolchildren from 11 to 14 years of age, enrolled in public schools. The history of bullying was evaluated by means of the Crozier; Dimmock adapted Questionnaire (1999). Self-esteem was determined by means of the Global Negative Self-Evaluation Scale (GSE). The normative orthodontic treatment need was determined by the Dental Health Component (DHC) and perceived need, by Aesthetic Component (AC) of the Index of Orthodontic Treatment Need (IOTN). Individual analyses were made of the associations with the history of bullying (outcome). Results: The variables that presented P ? 0.20 in the individual analyses were tested in a multiple logistic regression model, and variables with P ? 0.05 remained in the model. The odds ratios with the intervals of confidence were estimated. According to the results 72.5% of the schoolchildren reported a history of bullying. The schoolchildren who presented negative impact on the quality of life related to oral symptoms and negative self-esteem were observed to have 4.59 and 5.44 times more chance, respectively to report a history of bullying (P < 0.05), which did not suffer the influence of normative and perceived orthodontic treatment need. Conclusion: The history of bullying was not influenced by orthodontic treatment need, but by the low self-esteem of adolescents.